An integral vision of pain and its persistence: a whole-person, whole-system, salutogenic perspective - Johnson, Mark I. (Frontiers in Pain Research, 2025)
Persistent pain remains a significant global health challenge, with prevailing biomedical and biopsychosocial models often falling short in capturing its full complexity. These models frequently lack conceptual and contextual coherence, overlooking the deeply subjective, cultural, and systemic dimensions of pain. As a result, care can become fragmented and suboptimal. This perspective article introduces an integral vision of pain, grounded in the All Quadrants, All Levels (AQAL) framework, which offers a multidimensional approach that integrates subjective experience, objective mechanisms, cultural meaning, spiritual perspectives, and systemic structures. The article outlines how a simplified AQAL framework can serve as a heuristic tool to synthesise individual and collective dynamics—including psychological development and socio-environmental conditions—thereby informing a more comprehensive understanding of pain and its persistence. This includes recognising the role of painogenic environments and the impact of evolutionary mismatch in shaping pain experiences. This integral perspective reframes persistent pain within a salutogenic social model of health, adopting a whole-person, whole-system approach that supports the co-creation of compassionate, community-driven, and context-sensitive care. Ultimately, it reconceptualises persistent pain not merely as a disease state or clinical symptom, but as a dynamic, relational, and meaning-laden experience embedded within the evolving journey of life. This integral vision challenges reductionist paradigms, advancing a more coherent, salutogenic, and humanistic model for understanding and addressing persistent pain.